Rehabilitasi Jantung Berbasis Rumah yang Inovatif Setelah Infark Miokard: Laporan Kasus - Arini Utami; Ragil Aidil Fitriasari Addini; Alifa Dinda; Laksmita Dewi Adzillia; Mianti Nurrizky Sutejo (Pusat Riset dan Inovasi Nasional, 2026)
. Background: Cardiac rehabilitation (CR) is essential for improving functional recovery and reducing mortality after myocardial infarction (MI). However, participation in center-based CR remains low due to geographical, logistical, and socioeconomic barriers. Technology-assisted home-based cardiac rehabilitation (HBCR) offers a practical alternative to improve access and adherence. Case Presentation: A 58-year-old male recovering from ST elevation myocardial infarction (STEMI) following primary percutaneous coronary intervention (PCI) presented with reduced exercise tolerance, mild exertional dyspnea, and anxiety related to physical activity. Due to limited access to facility-based services, a six-week technology assisted HBCR program was initiated. Intervention: The program incorporated a mobile health application with telemonitoring, guided exercise sessions, daily vital sign tracking, lifestyle education, and weekly teleconsultation with a physiotherapist. Exercises included breathing techniques, progressive walking, low intensity aerobic training, and mobility exercises. Outcomes: After six weeks, the patient demonstrated meaningful improvements, with the 6-minute walk test increasing from 290 m to 395 m, resting heart rate decreasing from 82 bpm to 74 bpm, and reduced anxiety during activity. No adverse events were reported. Conclusion: Technology assisted HBCR appears to be a safe, feasible, and effective option for post MI rehabilitation, particularly for patients with limited access to conventional CR services.